2011
DOI: 10.4319/lom.2011.9.396
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of shallow water bathymetry, hydro‐optics, and benthos mapping techniques in Australian and Caribbean coastal environments

Abstract: Science, resource management, and defense need algorithms capable of using airborne or satellite imagery to accurately map bathymetry, water quality, and substrate composition in optically shallow waters. Although a variety of inversion algorithms are available, there has been limited assessment of performance and no work has been published comparing their accuracy and efficiency. This paper compares the absolute and relative accuracies and computational efficiencies of one empirical and five radiative-transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
245
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(259 citation statements)
references
References 38 publications
11
245
0
3
Order By: Relevance
“…[2009]; BRUCE- Klonowski et al [2007]; SAMBUCA- Wettle and Brando [2006]) and CRISTAL have shown particular merit when applied to hyperspectral imagery (contiguous spectral bands, resolution $5 nm) Dekker et al, 2011;Fearns et al, 2011;Garcia et al, 2014a;Goodman and Ustin, 2007;Hedley et al, 2009;Klonowski et al, 2007;Lee et al, 1999;Lesser and Mobley, 2007]. However, these previous studies were designed primarily to demonstrate bathymetric retrieval and benthic classification capabilities for shallow waters, typically less than 10 m depth, with little emphasis on the derived IOP values and downstream geophysical products such as CHL, SPM, and water clarity measures.…”
Section: Key Pointsmentioning
confidence: 99%
“…[2009]; BRUCE- Klonowski et al [2007]; SAMBUCA- Wettle and Brando [2006]) and CRISTAL have shown particular merit when applied to hyperspectral imagery (contiguous spectral bands, resolution $5 nm) Dekker et al, 2011;Fearns et al, 2011;Garcia et al, 2014a;Goodman and Ustin, 2007;Hedley et al, 2009;Klonowski et al, 2007;Lee et al, 1999;Lesser and Mobley, 2007]. However, these previous studies were designed primarily to demonstrate bathymetric retrieval and benthic classification capabilities for shallow waters, typically less than 10 m depth, with little emphasis on the derived IOP values and downstream geophysical products such as CHL, SPM, and water clarity measures.…”
Section: Key Pointsmentioning
confidence: 99%
“…The recent trend in analysis algorithms for shallow water benthic remote sensing is to seek a pixel-by-pixel best fit for reflectance from a forward-based radiative transfer model parameterised on benthic reflectance, depth, water optical properties [12,[14][15][16][17][18][19][20][21]. Such algorithms offer the promise of simultaneous derivation of depth, water optical properties and benthic class.…”
Section: Figurementioning
confidence: 99%
“…Many studies have used remote sensing to map seagrass meadows around the world [243][244][245][246][247][248][249][250][251]. Several recent studies also focused on the spatial and temporal variability of seagrasses [252][253][254][255][256][257][258][259].…”
Section: Seagrass Meadowsmentioning
confidence: 99%